Is neuromuscular inhibition detectable in elite footballers during the Nordic hamstring exercise? - Blandford, L.; Theis, N.; Charvet, I.; Mahaffey, R. (Clinical Biomechanics, 2018)
The presence of neuromuscular inhibition following injury may explain the high incidence of biceps femoris injury recurrence in elite (soccer) footballers. This phenomenon may be detectable in elite players during the Nordic hamstring exercise. Thus, the first purpose of this study was to assess biceps femoris muscle activation during this exercise in players with hamstring injury history. Additionally, following injury, observed increases in synergistic muscle activation may represent a protective mechanism to the presence of neuromuscular inhibition. Thus, the second purpose was to identify if the relative contributions of biceps femoris, and its synergists reflected a post-injury pattern of activation suggestive of these potentially compensatory neural mechanisms. Methods: Ten elite players with a history of hamstring injury and ten elite players without a history of hamstring injury, completed six repetitions of the Nordic hamstring exercise. During each trial, biceps femoris, semitendinosus and gluteus maximus muscle activations were collected at 90-30° and 30-0° of knee flexion. Findings: Biceps femoris activation was significantly higher at 90-30° of knee flexion compared to 30-0° (P < 0.001) but did not differ between the groups. In players with a history of injury, muscle activation ratios for the biceps femoris/semitendinosus (P = 0.001) and biceps femoris/gluteus maximus (P?=?0.023) were significantly greater at 30-0° of knee flexion than in the control group. Interpretation: Neuromuscular inhibition of the biceps femoris was not detected during the exercise within elite footballers, yet the relative contributions of biceps femoris and its synergists appear to change following injury.